2007
DOI: 10.1016/j.stem.2007.10.012
|View full text |Cite|
|
Sign up to set email alerts
|

The Plasminogen Fibrinolytic Pathway Is Required for Hematopoietic Regeneration

Abstract: Hematopoietic stem cells within the bone marrow exist in a quiescent state. They can differentiate and proliferate in response to hematopoietic stress (e.g., myelosuppression), thereby ensuring a well-regulated supply of mature and immature hematopoietic cells within the circulation. However, little is known about how this stress response is coordinated. Here, we show that plasminogen (Plg), a classical fibrinolytic factor, is a key player in controlling this stress response. Deletion of Plg in mice prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 28 publications
2
44
1
Order By: Relevance
“…Both VEGF-A and KitL can expand the CD11b? myeloid cell pool within the bone marrow [32] Plasmin regulates angiogenesis via MMP activation 135…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both VEGF-A and KitL can expand the CD11b? myeloid cell pool within the bone marrow [32] Plasmin regulates angiogenesis via MMP activation 135…”
Section: Resultsmentioning
confidence: 99%
“…We showed that MMP-9 participates in progenitor cell mobilization and the hematopoietic regeneration process within the BM by mediating the shedding of soluble forms of membrane-bound cytokines such as kit ligand (KitL, also known as stem cell factor or SCF) and induced SDF-1 [30]. These data regarding MMP-9 function were extended by a study that demonstrated that MMP-mediated release of KitL was blocked in Plg-deficient mice [32,33]. Indeed, proteinasemediated inactivation of cytokine signals such as c-kit/KitL and SDF-1/C-X-C chemokine receptor type 4 (CXCR4), which anchor hematopoietic progenitor stem cells (HPSCs) in the BM microenvironment, is central to the regulation of HPSC mobilization: the inactivation of these cytokine signals allows HPSCs to proliferate, migrate to the sinusoidal capillaries, and eventually enter the peripheral blood.…”
Section: Interplay Between Mmps and The Fibrinolytic System In The Rementioning
confidence: 92%
See 2 more Smart Citations
“…[12][13][14] The role of plm in guiding the cytokine storm is not well understood. Because plm can activate other proteases like metalloproteinases (MMPs) [15][16][17] and some MMP inhibitors can block processing of TNF-a and Fasligand (FasL), [18][19][20][21][22] we hypothesized that plm activation may control the cytokine storm and regulate the inflammatory response in murine models of aGVHD.…”
Section: Introductionmentioning
confidence: 99%